High-entropy sulfide material for negative electrode of lithium ion battery as well as preparation method and application of high-entropy sulfide material
By using high -entropy sulfide materials as lithium -ion battery negative electrode materials, the problems of traditional materials in terms of safety, rate, and cycle stability are solved, and higher electrochemical properties and longer battery life are achieved.
Patent Information
- Application Number
- CN202411448719.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
AI Technical Summary
The existing lithium-ion battery anode materials have problems such as poor safety, high speed, volume expansion, structural damage and lattice collapse, which affect the performance and life of the battery.
High-entropy sulfide materials are used as negative electrode materials for lithium-ion batteries. High-entropy sulfide precursors are prepared through the sol-gel method, and sulfur powder is added during high-temperature sintering to form stable nano-sized high-entropy sulfide materials.
It improves the electrochemical performance, rate performance and cycle stability of lithium-ion batteries, significantly increases the specific capacity and Coulombic efficiency, and extends the life of the battery.
Smart Images

Figure CN119330414A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of lithium-ion batteries, and in particular to a high-entropy sulfide material for a negative electrode of a lithium-ion battery, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high open circuit potential, high energy density, good cycle performance, and environmental friendliness. They are considered to be a promising energy source for electric vehicles and have been widely studied in the past two decades. Anode materials are an important component of lithium-ion batteries and directly affect the electrochemical performance of lithium-ion batteries. However, traditional carbon-based anode materials have always had problems with poor safety and high rate, which makes it difficult to meet the needs of modern society, especially in the field of electric vehicles. Some other potential anode materials, such as silicon-based and tin-based materials, have attracted widespread attention due to their higher theoretical capacity. However, the practical application of these anode materials is hindered by the drastic specific volume changes during Li insertion / extraction, resulting in poor cycle stability.
[0003] In recent years, high entropy materials have been observed to have remarkable physical and chemical properties in high entropy alloys and ceramic materials. High entropy materials are single-phase solid solution materials with nearly equal molar ratios of multiple components. The atoms of each component are randomly distributed in the crystal lattice to form a new stable single-phase solid solution rather than a phase-separated mixture. This not only allows high entropy materials to combine the advantages of each element, but also gives them unique properties as entropy increases, such as lattice distortion effect, "cocktail" effect and slow diffusion effect. The study of high entropy battery materials began with the development of high entropy metal oxides as lithium-ion battery anodes, which have better capacity and retention. This technology was subsequently expanded to include high entropy lithium-ion cathodes, which outperform commercial materials in energy density and rate capability. Recently, high entropy materials have also been explored for applications in lithium-ion solid electrolytes, showing ionic conductivity comparable to the best performing solid ion conductors.
[0004] The increase in the entropy of the mixed configuration caused by the increase in the elements of the high entropy material is enough to overcome the formation enthalpy of the single-phase compound and form a simple solid solution structure. However, a large number of studies have shown that the existing high entropy material sulfide has shortcomings such as volume expansion, structural damage, and lattice collapse during the cycle process. This phenomenon seriously affects the performance and life of the battery and also limits its application as anode materials for lithium-ion batteries. Summary of the invention
[0005] In view of this, the embodiments of the present application provide a high-entropy sulfide material for a negative electrode of a lithium-ion battery, and a preparation method and application thereof. The preparation method is simple and controllable, and the prepared high-entropy sulfide material for a negative electrode of a lithium-ion battery has good electrochemical properties. It has high rate performance in the field of lithium-ion batteries, and can effectively overcome the defects of poor ionic conductivity, low reversible capacity and poor cycle stability of lithium-ion battery materials.
[0006] The first aspect of the embodiment of the present application provides a method for preparing a high entropy sulfide material for a negative electrode of a lithium ion battery, comprising the following steps:
[0007] The metal salt, the complexing agent and potassium ferrocyanide are dissolved in deionized water, mixed and reacted to obtain a precursor, and the precursor is mixed with sulfur powder and calcined to obtain a high entropy sulfide material for a negative electrode of a lithium ion battery.
[0008] In some embodiments that may include the above embodiments, the following steps are specifically included:
[0009] Step 1: dissolving a metal salt and potassium citrate dihydrate in deionized water to obtain a solution A; dissolving potassium ferrocyanide in deionized water to obtain a solution B;
[0010] Step 2: Mix solution A and solution B, stir and place in an oven for drying to obtain precursor C;
[0011] Step 3: Add sulfur powder to the precursor C, mix and calcine in a tube furnace under inert atmosphere, wash three times by centrifugation with anhydrous ethanol and then dry to obtain a high entropy sulfide material for the negative electrode of a lithium-ion battery.
[0012] In some embodiments that may include the above embodiments, the morphology of the high entropy sulfide material for the negative electrode of the lithium ion battery is a cubic column structure.
[0013] In some embodiments that may include the above embodiments, the temperature rising process of calcination is: maintaining at 20° C. for 30 min, then heating to 600-800° C. at a heating rate of 4.5° C. / min and keeping the temperature for 10 h.
[0014] In some embodiments that may include the above embodiments, the metal salt is prepared by mixing and stirring zinc acetate, manganese acetate, lithium acetate, nickel acetate, sodium acetate in equal molar proportions.
[0015] In some embodiments that may include the above embodiments, in step 2, the stirring time is 1 to 2 hours; the drying temperature is 80° C., and the drying time is 12 to 24 hours.
[0016] In some embodiments that may include the above embodiments, in step 1, the ratio of the metal salt: potassium citrate dihydrate: deionized water is (1mmol-4mmol): (1mmol-4.4mmol): (20mL-60mL), preferably (1mmol-4mmol): (2mmol-4.4mmol): (30mL-60mL); or
[0017] The dosage ratio of the potassium ferrocyanide to deionized water is (1 mmol to 4 mmol): (20 mL to 50 mL).
[0018] In some embodiments that may include the above embodiments, in step three, the mass ratio of the precursor C to the sulfur powder is 1:(1-7).
[0019] In a second aspect, the embodiments of the present application also provide a high entropy sulfide material for a negative electrode of a lithium-ion battery prepared by the above method.
[0020] The third aspect of the embodiment of the present application also provides a lithium-ion battery negative electrode material, which is composed of the above-mentioned high entropy sulfide material for the lithium-ion battery negative electrode, the conductive agent Super P and PVDF in a mass ratio of 8:1:1, ground and mixed evenly in a mortar, and then coated on a copper foil with an appropriate amount of NMP, placed in a vacuum drying oven and dried at 80°C for 12 hours, and rolled and cut to obtain a battery negative electrode sheet.
[0021] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0022] 1. This application combines high entropy elements at the molecular level through the gel method. The unique gel structure of sol-gel can maximize the fusion of nanoparticles and surface area to promote reaction kinetics, and use the appropriate sintering temperature to form a stable nano-sized high entropy material, which is different from the simple mechanical mixing of sulfur-oxygen double anions and high entropy solid solution powder materials of rock salt-type high entropy oxides; this application helps to simultaneously optimize multiple properties of lithium-ion battery negative electrode materials;
[0023] 2. The present application uses high entropy sulfide as the negative electrode material of lithium-ion batteries. The high entropy material has high electrical conductivity and good electron transport properties, which helps to accelerate the embedding and de-embedding process of lithium ions and improve the charging and discharging efficiency of the battery; the unique columnar structure of the high entropy material is conducive to buffering volume expansion and lattice collapse during charging, reducing structural damage during the cycle process, thereby improving the cycle stability and life of the battery; the present application also creatively uses the sol-gel method to prepare a high entropy sulfide precursor, using potassium citrate as a complexing agent. Since the reactants are uniformly mixed at the molecular level when forming the gel, the uniformity at the molecular level can be obtained in a very short time, and the uniform doping of particles at the molecular level can be achieved, thereby improving the cycle performance and high specific capacity of the high entropy sulfide as a negative electrode material;
[0024] 3. The present application also adds sulfur powder during the high-temperature sintering process of the precursor and mixes them evenly to prepare a high-entropy sulfide lithium-ion battery negative electrode material. The charging specific capacity can reach 775.7 mAh / g at a current density of 100 mA / g in the first cycle, and the first cycle capacity retention rate is 61.64%, which significantly improves the specific capacity and coulombic efficiency of the lithium-ion battery, and has good rate performance and cycle stability. As a negative electrode material for lithium-ion batteries, it has broad application prospects;
[0025] 4. The high-entropy sulfide lithium-ion battery material provided in this application has the four core effects of high-entropy materials, such as high-entropy effect, lattice distortion, slow diffusion characteristics and "cocktail" effect; it can improve the technical problems of poor ion conductivity, low reversible capacity and poor cycle stability of lithium-ion battery materials;
[0026] 5. The raw materials prepared in this application are easily available, the preparation cost is low, the method is simple, the conditions are mild, the safety is high, and no large-scale equipment is required. The high-entropy sulfide lithium-ion battery negative electrode material prepared has excellent performance and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0028] Figure 1 XRD spectrum of the high entropy sulfide material for lithium ion battery negative electrode prepared in Example 1 of the present application;
[0029] Figure 2 The rate diagram of a lithium-ion battery made of a high-entropy sulfide material for the negative electrode of the lithium-ion battery prepared in Example 1 of the present application;
[0030] Figure 3 This is a SEM image of the high entropy sulfide material for lithium-ion battery negative electrode prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0032] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.
[0033] In the following examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.
[0034] Example 1
[0035] The method for preparing the high entropy sulfide material for the negative electrode of a lithium ion battery in this embodiment comprises the following steps:
[0036] Zinc acetate, manganese acetate, lithium acetate, nickel acetate, sodium acetate are mixed and stirred in equal molar ratios to obtain a mixed metal salt, 1 mmol of the mixed metal salt is taken and dissolved in 30 mL of deionized water together with 2 mmol of potassium citrate dihydrate to prepare solution A; 1 mmol of potassium ferrocyanide is then taken and dissolved in 20 mL of deionized water to obtain solution B; solutions A and B are mixed, stirred for 1 hour, and then placed in an oven at 80°C for 12 hours to obtain a precursor C; sulfur powder and precursor C are mixed in a mass ratio of 1:1, and calcined in a tube furnace under argon atmosphere, the calcination process is: 20°C is maintained for 30 minutes, then the temperature is increased to 700°C at a heating rate of 4.5°C / min and kept warm for 10 hours, the sintered precursor C is centrifugally washed three times with anhydrous ethanol and then dried for 12 hours, so as to obtain a high entropy sulfide lithium ion battery negative electrode material. Figure 1 XRD spectrum of the high entropy sulfide material for lithium ion battery negative electrode prepared in the embodiment of the present application; Figure 3 This is a SEM image of the high entropy sulfide material for the negative electrode of a lithium-ion battery prepared in an embodiment of the present application, and its morphology is a cubic column structure.
[0037] Example 2
[0038] The method for preparing the high entropy sulfide material for the negative electrode of a lithium ion battery in this embodiment comprises the following steps:
[0039] Zinc acetate, manganese acetate, lithium acetate, nickel acetate, sodium acetate are mixed and stirred in equal molar ratios to obtain a mixed metal salt, 1.5 mmol of the mixed metal salt is taken and dissolved in 35 mL of deionized water together with 2.4 mmol of potassium citrate dihydrate to prepare solution A; 1.5 mmol of potassium ferrocyanide is then taken and dissolved in 25 mL of deionized water to obtain solution B; solutions A and B are mixed, stirred for 1.2 hours, and then placed in an oven at 80°C for 14 hours to obtain a precursor C; sulfur powder and precursor C are mixed in a mass ratio of 2:1, and calcined in a tube furnace under argon atmosphere. The calcination process is: 20°C is maintained for 30 minutes, then the temperature is increased to 700°C at a heating rate of 4.5°C / min and kept warm for 10 hours, the sintered precursor C is centrifugally washed three times with anhydrous ethanol and then dried for 12 hours to obtain a high entropy sulfide lithium ion battery negative electrode material.
[0040] Example 3
[0041] The method for preparing the high entropy sulfide material for the negative electrode of a lithium ion battery in this embodiment comprises the following steps:
[0042] Zinc acetate, manganese acetate, lithium acetate, nickel acetate, sodium acetate are mixed and stirred in equal molar ratios to obtain a mixed metal salt, 2 mmol of the mixed metal salt is taken and dissolved together with 2.8 mmol of potassium citrate dihydrate in 40 mL of deionized water to prepare solution A; 2 mmol of potassium ferrocyanide is then taken and dissolved in 30 mL of deionized water to obtain solution B; solutions A and B are mixed, stirred for 1.4 hours, and then placed in an oven at 80°C for 16 hours to obtain a precursor C; sulfur powder and precursor C are mixed in a mass ratio of 3:1, and calcined in a tube furnace under argon atmosphere. The calcination process is: 20°C is maintained for 30 minutes, then the temperature is increased to 700°C at a heating rate of 4.5°C / min and kept warm for 10 hours, the sintered precursor C is centrifugally washed three times with anhydrous ethanol and then dried for 12 hours to obtain a high entropy sulfide lithium ion battery negative electrode material.
[0043] Example 4
[0044] The method for preparing the high entropy sulfide material for the negative electrode of a lithium ion battery in this embodiment comprises the following steps:
[0045] Zinc acetate, manganese acetate, lithium acetate, nickel acetate, sodium acetate and other molar ratios are mixed and stirred to obtain a mixed metal salt, 2.5 mmol of the mixed metal salt is taken and dissolved in 45 mL of deionized water together with 3.2 mmol of potassium citrate dihydrate to prepare solution A; 2.5 mmol of potassium ferrocyanide is then taken and dissolved in 35 mL of deionized water to obtain solution B; solutions A and B are mixed, stirred for 1.6 hours, and then placed in an oven at 80°C for 18 hours to obtain a precursor C; sulfur powder and precursor C are mixed in a mass ratio of 4:1, and calcined in a tube furnace under argon atmosphere. The calcination process is: 20°C is maintained for 30 minutes, then the temperature is increased to 700°C at a heating rate of 4.5°C / min and kept warm for 10 hours, and the sintered precursor C is centrifugally washed three times with anhydrous ethanol and then dried for 12 hours to obtain a high entropy sulfide lithium ion battery negative electrode material.
[0046] Example 5
[0047] The method for preparing the high entropy sulfide material for the negative electrode of a lithium ion battery in this embodiment comprises the following steps:
[0048] Zinc acetate, manganese acetate, lithium acetate, nickel acetate, sodium acetate are mixed and stirred in equal molar ratios to obtain a mixed metal salt, 3 mmol of the mixed metal salt is taken and dissolved in 50 mL of deionized water together with 3.6 mmol of potassium citrate dihydrate to prepare solution A; 3 mmol of potassium ferrocyanide is then taken and dissolved in 40 mL of deionized water to obtain solution B; solutions A and B are mixed, stirred for 1.8 hours, and then placed in an oven at 80°C for 20 hours to obtain a precursor C; sulfur powder and precursor C are mixed in a mass ratio of 5:1, and calcined in a tube furnace under argon atmosphere. The calcination process is: 20°C is maintained for 30 minutes, then the temperature is increased to 700°C at a heating rate of 4.5°C / min and kept warm for 10 hours, the sintered precursor C is centrifugally washed three times with anhydrous ethanol and then dried for 12 hours to obtain a high entropy sulfide lithium ion battery negative electrode material.
[0049] Example 6
[0050] The method for preparing the high entropy sulfide material for the negative electrode of a lithium ion battery in this embodiment comprises the following steps:
[0051] Zinc acetate, manganese acetate, lithium acetate, nickel acetate, sodium acetate are mixed and stirred in equal molar ratios to obtain a mixed metal salt, 3.5 mmol of the mixed metal salt is taken and dissolved in 55 mL of deionized water together with 4 mmol of potassium citrate dihydrate to prepare solution A; 3.5 mmol of potassium ferrocyanide is then taken and dissolved in 45 mL of deionized water to obtain solution B; solutions A and B are mixed, stirred for 2 hours, and then placed in an oven at 80°C for 22 hours to obtain a precursor C; sulfur powder and precursor C are mixed in a mass ratio of 6:1, and calcined in a tube furnace under argon atmosphere. The calcination process is: keep at 20°C for 30 minutes, then heat to 700°C at a heating rate of 4.5°C / min and keep warm for 10 hours, and the sintered precursor C is centrifugally washed three times with anhydrous ethanol and then dried for 12 hours to obtain a high entropy sulfide lithium ion battery negative electrode material.
[0052] Example 7
[0053] The method for preparing the high entropy sulfide material for the negative electrode of a lithium ion battery in this embodiment comprises the following steps:
[0054] Zinc acetate, manganese acetate, lithium acetate, nickel acetate, sodium acetate are mixed and stirred in equal molar ratios to obtain a mixed metal salt, 4 mmol of the mixed metal salt is taken and dissolved together with 4.4 mmol of potassium citrate dihydrate in 60 mL of deionized water to prepare solution A; 4 mmol of potassium ferrocyanide is then taken and dissolved in 50 mL of deionized water to obtain solution B; solutions A and B are mixed, stirred for 2 hours, and then placed in an oven at 80°C for 24 hours to obtain a precursor C; sulfur powder and precursor C are mixed in a mass ratio of 7:1, and calcined in a tube furnace under argon atmosphere, the calcination process is: 20°C is maintained for 30 minutes, then the temperature is increased to 700°C at a heating rate of 4.5°C / min and kept warm for 10 hours, the sintered precursor C is centrifugally washed three times with anhydrous ethanol and then dried for 12 hours, so as to obtain a high entropy sulfide lithium ion battery negative electrode material.
[0055] Test example
[0056] The material of Example 1 is used as the electrode material of lithium ion battery, and the specific preparation process is as follows:
[0057] (1) The material of Example 1 was mixed with the conductive agent Super P and PVDF in a mass ratio of 8:1:1, ground and mixed in a mortar, an appropriate amount of NMP was added and then coated on a copper foil, placed in a vacuum drying oven at 80° C. for 12 h, and rolled and cut into pieces to obtain a battery negative electrode sheet;
[0058] (2) Using a metal lithium sheet as a counter electrode, a 2016-type button battery was prepared in a glove box filled with argon gas, a celgard2250 diaphragm was used as the separator, and a 1M LiPF6 / EC:DEC (volume ratio 1:1) was used as the electrolyte. The battery performance of the prepared 2016-type button battery was tested on a blue power test system to test the electrochemical energy storage performance of the prepared lithium-ion battery;
[0059] (3) The charge and discharge range is 0.01-3V, and the charge and discharge rates are 0.1A / g, 0.2A / g, 0.3A / g, and 0.5A / g. The electrochemical energy storage performance of the prepared lithium-ion battery is tested, such as Figure 2 shown.
[0060] Depend on Figure 2 It can be seen that the lithium-ion battery prepared using the high entropy sulfide negative electrode material prepared in Example 1 has a discharge specific capacity of about 775.7 mAh / g, 619.5 mAh / g, 557 mAh / g, and 504.4 mAh / g at different charge and discharge current densities of 0.1 A / g, 0.2 A / g, 0.3 A / g, and 0.5 A / g, and the capacity retention rates are 91.86%, 97.62%, 98.92%, and 98.1%, respectively. This shows that the material has good cycle performance and high coulombic efficiency.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a high entropy sulfide material for a negative electrode of a lithium ion battery, characterized in that: The following steps are involved: The metal salt, the complexing agent and potassium ferrocyanide are dissolved in deionized water, mixed and reacted to obtain a precursor, and the precursor is mixed with sulfur powder and calcined to obtain a high entropy sulfide material for a negative electrode of a lithium ion battery.
2. The method for preparing the high entropy sulfide material for the negative electrode of a lithium ion battery according to claim 1, characterized in that: The specific steps include: Step 1: dissolving a metal salt and potassium citrate dihydrate in deionized water to obtain a solution A; dissolving potassium ferrocyanide in deionized water to obtain a solution B; Step 2: Mix solution A and solution B, stir and place in an oven for drying to obtain precursor C; Step 3: Add sulfur powder to the precursor C, mix and calcine in a tube furnace under inert atmosphere, wash three times by centrifugation with anhydrous ethanol and then dry to obtain a high entropy sulfide material for the negative electrode of a lithium-ion battery.
3. The method for preparing the high entropy sulfide material for the negative electrode of a lithium ion battery according to claim 1 or 2, characterized in that: The morphology of the high entropy sulfide material for the negative electrode of the lithium ion battery is a cubic column structure.
4. The method for preparing the high entropy sulfide material for the negative electrode of a lithium ion battery according to claim 1 or 2, characterized in that: The calcination temperature rise process is: maintain at 20°C for 30 minutes, then increase the temperature to 600-800°C at a heating rate of 4.5°C / min and keep the temperature for 10 hours.
5. The method for preparing the high entropy sulfide material for the negative electrode of a lithium ion battery according to claim 1 or 2, characterized in that: The metal salt is prepared by mixing and stirring zinc acetate, manganese acetate, lithium acetate, nickel acetate, sodium acetate in equal molar proportions.
6. The method for preparing the high entropy sulfide material for the negative electrode of a lithium ion battery according to claim 2, characterized in that: In step 2, the stirring time is 1 to 2 hours; the drying temperature is 80° C., and the drying time is 12 to 24 hours.
7. The method for preparing a high entropy sulfide material for a negative electrode of a lithium ion battery according to claim 2, characterized in that: In step 1, the ratio of the metal salt: potassium citrate dihydrate: deionized water is (1 mmol to 4 mmol): (1 mmol to 4.4 mmol): (20 mL to 60 mL); or The dosage ratio of the potassium ferrocyanide to deionized water is (1 mmol to 4 mmol): (20 mL to 50 mL).
8. The method for preparing a high entropy sulfide material for a negative electrode of a lithium ion battery according to claim 2, characterized in that: In step 3, the mass ratio of the precursor C to the sulfur powder is 1:(1-7).
9. A high entropy sulfide material for a negative electrode of a lithium ion battery prepared by the method according to any one of claims 1 to 8.
10. A negative electrode material for a lithium ion battery, characterized in that: The high entropy sulfide material for the negative electrode of the lithium-ion battery according to claim 9 is mixed with the conductive agent Super P and PVDF in a mass ratio of 8:1:1, ground and mixed evenly in a mortar, an appropriate amount of NMP is added and then coated on a copper foil, placed in a vacuum drying oven at 80°C for 12 hours, and the battery negative electrode sheet is obtained after rolling and cutting.